Metabolomics Pilot Study Identifies Desynchronization of 24-H Rhythms and Distinct Intra-patient Variability Patterns in Critical Illness: A Preliminary Report - Lusczek, Elizabeth R.; Parsons, Lee S.; Elder, Jesse; Harvey, Stephen B.; Skube, Mariya; Muratore, Sydne; Beilman, Greg; Cornelissen-Guillaume, Germaine (Frontiers in Neurology, 2020)
Background: Synchronized circadian rhythms play a key role in coordinating physiologic health. Desynchronized circadian rhythms may predispose individuals to disease or be indicative of underlying disease. Intensive care unit (ICU) patients likely experience desynchronized circadian rhythms due to disruptive environmental conditions in the ICU and underlying pathophysiology. This observational pilot study was undertaken to determine if 24-hour rhythms are altered in ICU patients relative to healthy controls by profiling 24-hour rhythms in vital signs and plasma metabolites. Methods: We monitored daily rhythms in 5 healthy controls and 5 ICU patients for 24 hours. Heart rate and blood pressure were measured every 30 minutes, temperature was measured every hour, and blood was sampled for mass spectrometry-based plasma metabolomics every 4 hours. Bedside sound levels were measured every minute. 24-hour rhythms were evaluated in vitals and putatively identified plasma metabolites individually and in each group using the cosinor method. Results: ICU patient rooms were significantly louder than healthy controls’ rooms and average noise levels were above EPA recommendations. Healthy controls generally had significant 24-hour rhythms individually and as a group. While a few ICU patients had significant 24-hour rhythms in isolated variables, no significant rhythms were identified in ICU patients as a group, except in cortisol. This indicates a lack of coherence in phases and amplitudes among ICU patients. Finally, principal component analysis of metabolic profiles showed surprising patterns in plasma sample clustering. Each ICU patient’s samples were clearly discernable in individual clusters, separate from a single cluster of healthy controls. Conclusions: In this pilot study, ICU patients’ 24-hour rhythms show significant desynchronization compared to healthy controls. Clustering of plasma metabolic profiles suggests that metabolomics could be used to track individual patients’ clinical courses longitudinally. Our results show global disordering of metabolism and the circadian system in ICU patients which should be characterized further in order to determine implications for patient care.